Speak the truth, laughing : nine stories and a novella, House arrest - Zwi, Rose (Spinifex, 2002)
Rose Zwi's stories embrace people from different countries and cultures drawn together by a common humanity: a political activist under house-arrest to the child of immigrant parents caught between two cultures; a city-educated woman returning to the arid homeland of her tribal grandfather.